Strategi Benchmarking Kepala Sekolah dalam Meningkatkan Kinerja Guru - Rizza Abrori; M. Miftahul Ulum (Excelencia: Journal of Islamic Education & Management, 2024)
The principal as a leader must have a clear vision and mission for the institution he leads. This benchmarking strategy allows the principal to conceptualize a plan that will serve as the starting point for determining the direction the school will take. The purpose of this paper is to find out the formulation of the principal's benchmarking strategy in improving teacher performance at SDN 1 Singosaren Ponorogo, to find out the implementation of the principal's benchmarking strategy to improve teacher performance at SDN 1 Singosaren Ponorogo, to find out the control of the principal's benchmarking strategy in improving teacher performance at SDN 1 Singosaren Ponorogo. The writing method used is qualitative writing with the type of case study writing. This writing was done in the location of SDN 1 Singosaren. As for data collection through observation, interviews and documentation. The data analysis used in this study is the data analysis model of Miles and Huberman. Based on the findings of researchers regarding the benchmarking strategy for school principals in improving teacher performance at SDN 1 Singosaren Ponorogo through several stages, namely formulation, implementation and control. First, the formulation: 1) oriented towards the school's vision and mission, 2) understand the characteristics of the school institution itself, 3) form teamwork, 4) determine a superior institution to become a benchmark, 5) determine the subject of benchmarking. Second, implementation is carried out by conducting a comparative study at the destination institution using interview/discussion methods, observation and documentation to collect data. The data for the benchmarking study will then be adjusted and selected by considering several factors, including: culture, human resource capabilities, leadership, organization, administration, and school programs. Third, control is carried out through close communication between leaders, subordinates and all education stakeholders, which can make strategy implementation more effective because it allows early detection of various obstacles faced by subordinates.